FACTORS RELATED TO HEALTH PROMOTION BEHAVIORS OF STAFFS IN KANCHANABURI RAJABHAT UNIVERSITY - Sanghirun, Manika (Academic Journal of Thailand National Sports University, 2020)
The research of “factors related to health promotion behaviors of staffs in Kanchanaburi Rajabhat University” aims to study factors related to health promotion behaviors of officers in Kanchanaburi Rajabhat University. This research is a descriptive research (correlational research design) which studies the relating of predisposing factors: knowledge, attitude, perception of benefit, self-efficacy toward health promotion behaviors, including enabling factors of resources and environment for health promotion, health promotion policy of the agency, reinforcing factors of receiving information from media, the supporting of health promotion behaviors from family members and colleagues who are selected by multi-state sampling about 149 academic staffs and support staffs of 249 staffs from 5 faculties. The collecting data are about 60.52% which are from questionnaires, the reliability and validity of which are found at 0.84 and 1. The findings revealed that: The correlation coefficient between predisposing factors and health promotion behaviors of staffs had positively correlated with health promotion behaviors at the significant level of .05 (r = .383), the perception of benefit had positively correlated at the significant level of .05 (r = .365), self-efficacy toward health promotion behaviors had positively correlated at the significant level of .05 (r = .540), and the attitude had positively correlated at the significant level of .05 (r = .058). The correlation coefficient between enabling factors and health promotion behaviors of staffs in resources and environment for health promotion factors had positively correlated at the significant level of .05 (r = .238), and the health promotion policy of the agency had positively correlated at the significant level of .05 (r = .217). The correlation coefficient between perception of health promotion behaviors of staffs in reinforcing factors of receiving information from media had positively correlated at the significant level of .05 (r = .482), and the supporting of health promotion behaviors from family members and colleagues had positively correlated at the significant level of .05 (r = .532). Moreover, it could be better to construct the self-efficacy of health promotion behaviors and the supporting of health promotion behaviors from family members and colleagues of health promotion behaviors of staffs in Kanchanaburi Rajabhat University to be well-being development for healthy life.